Possibilities of Radionuclide-Tomo-Ventriculorgraphy with Labeled 99m Technetium of Sodium Diphosphate Decahydrate in Assessing Mechanical Dyssynchrony of Myocardium and Intracardiac Hemodynamics in Ventricular Arrhythmias in Children - Zavadovsky K. V. Konstantin Valerievich (Radiation Technologies in Medicine, 2015)
Title screen